(untitled) (Biological Sciences - PJSIR, 2022)
The thermal analysis ofFe(II), Ni(IJ) and Cu(lI) complexes with 1,3,5- trimethyl hexahydro-triazine (TMAZ) and 1,4,7- triazacyclononane (TACN) were studied by microanalysis, TG and DTA techniques. Metal - TMAZ complexes show somewhat similarTG and DTA profiles when heated in Nz atmosphere. An endothermic peak appears in the range 60-130°C which attributed to liberation of the organic ligand. TACN complexes show exothermic peak in the range 200- 245°C proceded to endothermic peak for dehydration of metal chelates in the range 125-155°C. The exothermic peak, corresponding to rapid mass-loss in TG curves, which may be due to oxidation reduction reaction. A relative thermal stability of metal complexes is reported.